The Effect of Animated Videos on Creativity in Science Learning of Class V Students About Changes in Objects in Elementary School 067256 Medan Marelan District Academic Year 2020-2021 - Nur Aulia (Berpusi Publishing, 2022)
This study aims to determine whether the use of animated video media can affect students' creativity or not. The research method used is quantitative research method with experimental research type. The population and sample in this study were fifth grade students at SDN 067256 Medan Marelan sub-district totaling 30 students in the control class and 30 students in the experimental class. Based on the t-test Post test, it is known that the average experimental learning outcomes are 96.23 and the control class learning average is 70.73 so it can be concluded that the experimental class learning outcomes are 25.86 greater than the control class. . From the table, it is known that the t count is 17, 515 with a significance of 0.000. The t table of 58 db at a significant level of 5% is 1.671. If the value of t count > t table ( 17, 515> 1.671) and the significance value is less than 0.05 (0.000 < 0.05). So it can be concluded that there is an effect of animated video on the creativity of science learning for fifth grade students about changes in the shape of objects at SDN 067256, Medan Marelan District. Based on the results of this study, students are expected to be able to improve learning outcomes by fostering interest in learning, for example by paying great attention when the learning process takes place, daring to ask questions, having great curiosity.